Buy-it-Now Prices in eBay Auctions The Field in the Lab - Radosveta Ivanova-Stenzel; Tim Grebe; Sabine Kröger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In eBay s Buy-it-Now auctions sellers can post prices at which buyers can purchase a good prior to an auction. We study how sellers set Buy-it-Now prices when buyers have independent private values for a single object for sale. We test the predictions of a model by combining the real auction environment (eBay auction platform and eBay traders) with the techniques of lab experiments. We observe that the eBay auction format supports deviations from truthful bidding leading to auction prices below those expected in second price auctions. Our proposed extension of the model results not only in a better fit of the data but provides new predictions to test. We find the information that is available on eBay is correlated with the level that eBay auction prices deviate from prices based on true value bidding. Sellers adjust their Buy-it-Now prices according to this information in the direction predicted by the model. They increase their BIN price when facing a population of more experienced buyers, when observing a higher number of submitted bids or more last-minute bidding from at least one bidder. More experienced sellers also ask for higher BIN prices.
Keywords: C91; D44; D82; 330